Long-term Oncologic Results and Voice Outcomes in Patients With Glottic Cancer After Modified Type III Cordectomy. (November 2022) - Liu, Chin-Hsuan; Chien, Pei-Ju; Hung, Li-Ting; Wang, Li-Mei; Kao, Ya-Chuan; Tsai, Yueh-Ju; Chu, Pen-Yuan
Objective: Transoral laser microsurgery and radiotherapy provide high and comparable cure rates for the treatment of early glottic cancer. However, the voice outcomes after treatment remain controversial. A modified type III cordectomy technique was proposed in 2006, and preliminary results showed it to be an oncologically safe method with satisfactory voice outcomes. This study aimed to evaluate oncologic and voice outcomes after long-term follow-up of these patients. Study Design: Retrospective cohort study. Setting: Tertiary care academic center. Methods: Between 2006 and 2018, 42 patients with glottic cancer underwent a modified type III cordectomy. This technique resected the tumor and upper part of the vocal folds and preserved the lower part of the vocalis muscle as a scaffold to improve glottis closure. The oncologic results and voice outcomes were evaluated at a median follow-up of 68 months. Results: The primary tumor stages included 13 T1 (31%), 26 T2 (64%), and 3 T3 (7%). Eight patients (19%) had local recurrence, and 6 underwent successful salvage with transoral laser microsurgery with or without postoperative radiotherapy with laryngeal preservation. The 5-year rate of local control was 80%; laryngeal preservation, 95%; overall survival, 89%; and disease-specific survival, 97%. The final laryngeal preservation rate was 95% (40/42). The voice outcomes were satisfactory and comparable to those of patients who underwent type I and II cordectomies. Conclusion: The modified type III cordectomy has been proven to be an oncologically safe method with satisfactory voice outcomes after long-term follow-up in selected cases of early glottic cancer.